(untitled) (Fiep Bulletin - online, 2016)
The changes in the last century in our society and the world, socio-economic and cultural changes have reflected the occurrence of chronic conditions like high blood pressure (HT) and diabetes mellitus (DM), both an issue of extreme importance in several countries that need to be early diagnosed, for they can be controlled to avoid future complications. In this context, knowing the causes of abandonment of treatment is essential to develop strategies for compliance with and continuity in the HIPERDIA program. The objective is to identify the reasons that lead to the abandonment and the approaches adopted by patients regarding their health in the HIPERDIA program in a basic health unit of Foz do Iguaçu PR. This is an exploratory and qualitative research, and its sample consisted of 20 users registered in HIPERDIA based on a survey with patients who did not attend follow-up in the Morumbi III Basic Health Care Unit (BHCU) of Foz do Iguaçu PR for more than 4 months. The data collection tool questionnaire was about questions on the reasons that led to the abandonment of treatment and procedures adopted to control the disease. From the patients enrolled in the program, 198 (38.29%) did not attend the HIPERDIA program for nearly four months. Treatment abandonment is a common problem and probably the biggest challenge faced now for adequate control of hypertension and diabetes mellitus. It was possible to identify the need for knowledge improvement among the population served by the Morumbi III BHCU, most of which could not explain the possible consequences of non-compliance with the treatment. Lack of time was the main difficulty to follow the treatment of HT and DM as individuals set several other activities as priority.